Simulation of Building Evacuation: Performance Analysis and Simplified Model - Alginahi, Yasser M.; Kabir, M. Nomani (The Science and Information (SAI) Organization Limited, 2016)
rowd evacuation from industrial buildings, factories, theatres, protest areas, festivals, exhibitions and religious/sports gatherings is very crucial in many dangerous scenarios, such as fire, earthquakes, threat and attacks. Simulation of crowd evacuation is an integral part of planning for emergency situations and training staff for crow management. In this paper, simulation of crowd evacuation for a large building-hall is studied using a popular crowd-simulation software BuildingEXODUS. Evacuation of the fully occupied hall is simulated with eleven test cases using the different experimental setups in the software. The results of the different evacuation scenarios are analysed to check the effect of various parameters involved in the evacuation performance. Finally, using the evacuation test results, simplified models are developed. It is found that the model outputs are in good agreement with the simulation results. Therefore, the models can readily be used for fast computation of the evacuation results without running the actual simulation.